Correction: Kolesar et al. Role of Nse1 Subunit of SMC5/6 Complex as a Ubiquitin Ligase. Cells 2022, 11, 165 - Kolesar, Peter; Stejskal, Karel; Potesil, David; Murray, Johanne M.; Palecek, Jan J. (Cells (Basel, Switzerland), 2024)
In the original publication [...]